Pengembangan LKS Berbasis Etnomatematika untuk Memfasilitasi Kemampuan Representasi Matematis - Astuti, Novita; Jana, Padrul; Marsiyam, Marsiyam (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2022)
The mathematical representation ability of junior high school (SMP) students is still not optimal. This study aims to develop student activity sheets (LKS) with valid, practical and effective criteria based on ethnomathematics which can specifically facilitate students' mathematical representation abilities. The worksheets were developed in order to facilitate students' mathematical representation skills through pictures and symbols. This study uses research and development (R&D) methods by applying the ADDIE model, namely: analysis (analysis), design (design), development (development), implementation (implementation), and evaluation (evaluation). The LKS was tested on 32 grade 7B students of SMP N 1 Mlati for the 2020/2021 academic year. The instruments used were interview guide sheets, material expert and media expert assessment questionnaires, student and teacher response questionnaires, learning implementation observation sheets, and mathematical representation ability test questions. Based on the results of the study, it was obtained: (1) LKS was declared